Game outcome uncertainty in the English Premier League. Do German fans care? - Schreyer, D.; Schmidt, S. L.; Torgler, B. (Journal of Sports Economics, 2018)
Despite the increasing internationalization of marketing activities by professional sporting clubs, previous research exploring the role of game outcome uncertainty (GOU) in spectator demand has been exclusively conducted within national contexts. As a consequence, very little is known about the preferences of international television (TV) spectators watching games from abroad. Hence, this study analyzes all 571 English Premier League (EPL) games broadcast in Germany between the seasons 2011-2012 and 2015-2016 in order to explore whether TV demand for transnational football games is affected by GOU. In line with the prominent uncertainty of outcome hypothesis, the results of this analysis reveal a significant and positive relation between German EPL demand and GOU. This result, however, is not consistent for male and female spectators.